PENGARUH SELF-EFFICACY, GROWTH MINDSET, DAN GRIT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN MATEMATIKA - Rohim, Abdur; ‘Adna, Syita Fatih; Feriyanto, Feriyanto; Subanji, Subanji; Sudirman, Sudirman (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
This study aims to assess the influence of academic self-belief (self-efficacy) and personal perseverance (grit) in relation to students' understanding of mathematics. A quantitative approach was employed using a correlational design. The participants consisted of 29 university students selected through a cluster random sampling technique. Data were collected using a Likert-scale questionnaire. The analysis included descriptive statistics, classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity), and hypothesis testing through multiple linear regression analysis. The findings revealed that both self-efficacy and grit had a statistically significant and positive impact on learning outcomes (p < 0.05), whereas growth mindset did not show a meaningful influence (p > 0.05). All three psychological factors contributed significantly to students’ critical thinking skills, with a coefficient of determination (R²) of 0.909, indicating that 90.9% of the variance in critical thinking ability could be explained by the model. Therefore, it can be concluded that students’ critical thinking performance in mathematics is substantially shaped by psychological traits such as self-efficacy and grit.